APPLICATION OF FUZZY LOGIC IN PREDICTING REQUIREMENTSFUEL OIL FOR SUPPLY STOCK SEAING AT THE BUNGUS OCEANFISHERY PORT - Mardeni Mardeni; Bustari Bustari; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT               Fuel oil is the aspect that is most prepared before going to sea. In meeting the demand for fluctuating fuel oil demand, prediction is needed, so that it can predict the supply to meet the required amount. This study aims to predict the amount of fuel oil inventory each month by using fuzzy logic to meet the needs of fishing supplies.               The results showed that the prediction of fuel oil had increased compared to the supply of fuel oil in the previous year. The total supply of fuel oil in 2019 was 1866 tons, while the prediction of fuel oil inventories for 2020 was 1974 tons. The results of this fuel oil prediction were tested using MAPE (Mean Absolute Presentage Error) to get the accuracy value. The MAPE value obtained is 7.68% which is considered accurate and acceptable to determine the prediction results of fuel oil inventories.Keywords: Prediction of fuel oil inventory, fishing supplies, fuzzy logic